'Piffling' Feminism in Joyce Waring's Autobiographical Texts. Issue 2 (3rd July 2019) - Smit, Lizelle
Abstract : This article investigates the writing strategies utilized by Joyce Waring in her three autobiographical texts, I'm no Lady (1956), Sticks and Stones (1969) and Hot Air (1977) to critique men and patriarchy. Due to a variety of cultural, social and political factors, there is a paucity of South African feminist writing published from the 1950s to the 1980s, making Joyce Waring's feminist critique of gendered society, men and patriarchy rare. However, as this article suggests, when read retrospectively, Waring's feminist criticism, albeit unusual for the period in question, fails in its critique because of its wilful dismissal of the myriad of class and racial factors inherent to women's lived and social experiences in apartheid South Africa. Waring's feminism thus conforms to what Nadine Gordimer describes as the 'piffling' white feminism of the period. However, as problematic Waring's writing on gender is, her voice remains important as part of the construction of an archive of women's life writing of the period and in guarding against the sanitizing of South African (literary) history and erasing of the specificities of past atrocities.